Monitoring of Gadolinium-BOPTA Uptake into the Vessel Wall during Magnetic Resonance (MR)-Guided Angioplasty of the Peripheral Arteries with a Paclitaxel/Gadolinium-BOPTA-Coated Balloon: An Experimental Study at 3 Tesla - Neizel, M.; Ruebben, A.; Weiss, N.; Günther, R. W.; Kelm, M.; Krombach, G. A. (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2014)
Purpose: The success of paclitaxel distribution within the vessel wall during paclitaxel-coated balloon angioplasty to prevent restenosis cannot be monitored under X-ray guidance. The aim of this pilot study was to demonstrate the feasibility of monitoring Gadolinium-BOPTA delivery within the vessel wall during magnetic resonance (MR)-guided paclitaxel/Gadolinium-BOPTA-coated balloon angioplasty of the peripheral arteries.Materials and Methods: 6 pigs (47 ± 2 kg) were investigated. All experiments were performed using a 3 Tesla MR scanner. MR-guided bilateral angioplasty of the iliac arteries was performed using a paclitaxel/MR contrast agent-coated balloon catheter. The feasibility of monitoring the delivery of Gadolinium-BOPTA to the vessel wall was assessed in 4 animals. In two additional animals, bilateral stenosis was surgically induced in the iliac arteries. Delivery of paclitaxel to the vessel wall was monitored using a 3 D T1-weighted gradient echo (GE) sequence for delineation of the vessel wall. Normalized signal intensity (SI) of the vessel wall was measured before and repeatedly after the intervention for 45 min. in all animals.Results: Paclitaxel/gadolinium-BOPTA-coated balloon angioplasty was successfully accomplished in all iliac arteries (n = 12). In animals with stenosis MR-angiography demonstrated successful dilatation (n = 4). The normalized SI of the vessel wall on T1-weighted GE images significantly increased after the intervention in all animals with and without stenosis for more than 45 min. (p < 0.001).Conclusion: Monitoring of Gadolinium-BOPTA into the vessel wall during MR-guided coated balloon angioplasty is feasible. This is a first step towards providing a tool for the online control of homogenous drug delivery after paclitaxel-coated balloon angioplasty.Key Points:• Monitoring of gadolinium-BOPTA uptake into the vessel wall during MR-guided coated balloon angioplasty is feasible.• Endovascular MR-guided interventions on a 3 Tesla MR scanner are feasible.• This is a first step towards providing a tool for online control of homogenous drug delivery after paclitaxel-coated balloon angioplasty.Citation Format:• Neizel M, Ruebben A, Weiss N et al. Monitoring of Gadolinium-BOPTA Uptake into the Vessel Wall during Magnetic Resonance (MR)-Guided Angioplasty of the Peripheral Arteries with a Paclitaxel/Gadolinium-BOPTA-Coated Balloon: An Experimental Study at 3 Tesla. Fortschr Röntgenstr 2014; 186: 388 – 393
Keywords: interventional MRI; angioplasty; drug-eluting balloon; vascular; MR imaging